Feeling of Professional Burnout among Contractual Teachers in Inclusive Education in Cameroon: an Analysis of the Engaging Human Condition of the Cameroonian Teacher at Work. - Achille, Tadaha Moffo; Marlyse, Mamfouo Audrine; Mama, Mbouombouo (Journal of Advanced Psychology, 2025)
Purpose: The feeling of burnout of the worker is a precautionary element in understanding the motivation of workers engaged in the care and support of vulnerable individuals. Methodology: A documentary analysis and an exploratory survey of teachers contracted by the State of Cameroon and assigned to 'inclusive schools' in the Littoral/West-Cameroon region allowed us to address the following question: how do contractual teachers experience their integration into the inclusive school within the Cameroonian context? In other words, what explanations do Cameroonian contractual teachers give for their feelings of professional burnout? Results: this article presents the findings of this empirical research and outlines the implications for enhancing the understanding of the ongoing commitment of our contractual teachers in the context of school inclusion and their predisposition to feelings of professional burnout. Results: this article presents the outcome of this empirical research and discusses the implications for enhancing the understanding of the ongoing commitment of our contract teachers in the context of inclusive education and their predisposition to feelings of professional burnout. Unique Contribution to Theory and Practice: raising awareness about the emotional state of contract teachers in the context of inclusive education in relation to the behavioral adaptation difficulties of students, the imbalance between professional demands and their personal competencies in the teaching task, and the lack of perceived social support from the educational community. It is therefore urgent, in light of the Job Demands-Resources (JD-R) model by Bakker and Demerouti (2007), to review the formulation of demands (efforts, requirements/workloads) and the quality of resources (specialized training, remuneration conditions, better planning and distribution of tasks...) in order to increase the involvement possibilities of contractual teachers in Cameroon within the context of inclusive education.